A reference guide to American English idioms (United States, 2010)
In the Loop is divided into three parts: Part 1, “Idioms and Definitions”; Part 2, “Selected Idioms by Category”; and Part 3, “Classroom Activities.” The idioms are listed alphabetically in Part 1. Part 2 highlights some of the most commonly used idioms, grouped into categories. Part 3 contains classroom suggestions to help teachers plan appropriate exercises for their students. There is also a complete index at the back of the book listing page numbers for both main entries and cross-references for each idiom.
Keywords: Tiếng Anh,English language; Sách giáo khoa cho người nước ngoài,Thành ngữ,Idiomatic,Textbooks for foreign speakers